Impact of Preoperative Malnutrition on Postoperative Long-Term Outcomes of Patients With Pancreatic Head Cancer. Issue 1 (18th March 2021) - Lee, Boram; Han, Ho-Seong; Yoon, Yoo-Seok
Abstract : Objective: To evaluate the association between preoperative malnutrition and long-term outcomes in patients with pancreatic head cancer who underwent curative pancreatoduodenectomy (PD). Methods: From 2004 to 2018, 228 consecutive patients who underwent curative PD for pancreatic ductal adenocarcinoma were included. Preoperative malnutrition was defined by the Global Leadership Initiative in Malnutrition criteria. It is based on both phenotypic criteria (weight loss, low body mass index, and reduced muscle mass) and etiologic criteria (reduced intake or assimilation and inflammation). Results: Seventy-five (32.9%) of 228 patients were classified as suffering from malnutrition. Preoperative malnutrition was associated with an increased risk of estimated blood loss (mL) (816.7 ± 875.2 vs 593.1 ± 489.9, P = 0.015) and longer hospital stay (days) (27.3 ± 15.7 vs 22.9 ± 17.7, P = 0.045). The median follow-up period was 24.5 months. The malnutrition group had poor overall survival compared with "without (WO)-malnutrition" group ( P = 0.001) at 1 year (66.3% vs 81.3%), 3 years (18.0% vs 51.8%), and 5 years (12.0% vs 39.3%). The malnutrition group showed poor disease-free survival and cancer-specific survival compared with WO-malnutrition group ( P = 0.001) at 1 year (38.9% vs 66.7%) and (69.0% vs 88.7%), 3 years (11.5% vs 45.1%) and (21.1% vs 61.6%), and 5 years (11.5% vs 37.3%) and (14.1% vs 51.2%). In multivariate analysis, the preoperative malnutrition was found to be the predictor of poor prognosis (harzard ratio = 2.29, 95% confidence interval = 1.60–3.29, P = 0.001). Conclusions: Preoperative malnutrition is associated with poor prognosis in patients who underwent curative PD for pancreatic head cancer. Abstract : Mini-abstract: Preoperative malnutrition occurs frequently in the patient with pancreatic head cancer. In this study, preoperative malnutrition has been shown to be associated with poor long-term survival outcomes.